2008
DOI: 10.1007/s10661-008-0462-8
|View full text |Cite
|
Sign up to set email alerts
|

Using the Sediment Quality Triad to characterize baseline conditions in the Anacostia River, Washington, DC, USA

Abstract: The Sediment Quality Triad (SQT) consists of complementary measures of sediment chemistry, benthic community structure, and sediment toxicity. We applied the SQT at 20 stations in the tidal portion of the Anacostia River from Bladensburg, MD to Washington, DC to establish a baseline of conditions to evaluate the effects of management actions. Sediment toxicity was assessed using 10-day survival and growth tests with the freshwater amphipod, Hyalella azteca and the midge, Chironomus dilutus. Triplicate grabs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Numerous studies have documented elevated levels of chemical contaminants in sediments, surface waters and fish tissue throughout the river (Foster et al 2000;McGee et al 2009;Velinsky et al 1994;Wade et al 1994) and their impact to fish and benthic biota (McGee et al 2009;Pinkney et al 2004;Schlekat et al 1994;Velinsky and Cummins 1996). In the past decade, the District of Columbia and State of Maryland have implemented assessments and control programs that are geared to reducing the inputs of many contaminants and begin to restore the river.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented elevated levels of chemical contaminants in sediments, surface waters and fish tissue throughout the river (Foster et al 2000;McGee et al 2009;Velinsky et al 1994;Wade et al 1994) and their impact to fish and benthic biota (McGee et al 2009;Pinkney et al 2004;Schlekat et al 1994;Velinsky and Cummins 1996). In the past decade, the District of Columbia and State of Maryland have implemented assessments and control programs that are geared to reducing the inputs of many contaminants and begin to restore the river.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have reported changes in larval behaviors in response to exposure to heavy metals (LeFauve & Connaughton, 2017), alcohol (Clayman et al, 2017), and endocrine disruptors (Bernardo & Connaughton, 2022;Crowley-Perry et al, 2021;Gould et al, 2017;Gould et al, 2019). (DOEE, 2019;McGee et al, 2009;Murray et al, 2015;Velinsky et al, 2011;Wade et al, 1994;Wilson, 2019). Importantly, we recently identified siloxanes in water samples collected from this waterway (Wilken et al, 2020).…”
mentioning
confidence: 65%
“…These water samples were collected from the urban鈥恑nfluenced Anacostia River, Washington, DC. The Anacostia River is one of the most polluted rivers in the United States with chemicals consistently identified in water and/or sediment samples including polycyclic and monocyclic aromatic hydrocarbons and PCBs (DOEE, 2019; McGee et al, 2009; Murray et al, 2015; Velinsky et al, 2011; Wade et al, 1994; Wilson, 2019). Importantly, we recently identified siloxanes in water samples collected from this waterway (Wilken et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Benthic invertebrate survey was carried out along with the sediment sampling according to McGee et al (2009). Invertebrate samples were taken from soft sediment and sieved through a 250-渭m mesh and then transferred into a jar and stored in 4% formalin solution.…”
Section: Determination Of Metric Valuesmentioning
confidence: 99%